Microwave assisted synthesis and characterisation of a zinc oxide/tobacco mosaic virus hybrid material. An active hybrid semiconductor in a field-effect transistor device - Sanctis, Shawn; Hoffmann, Rudolf C.; Eiben, Sabine; Schneider, Jörg J. (Beilstein Journal of Nanotechnology, 2015)
Tobacco mosaic virus (TMV) has been employed as a robust functional template for the fabrication of a TMV/zinc oxide field effect transistor (FET). A microwave based approach, under mild conditions was employed to synthesize stable zinc oxide (ZnO) nanoparticles, employing a molecular precursor. Insightful studies of the decomposition of the precursor were done using NMR spectroscopy and material characterization of the hybrid material derived from the decomposition was achieved using dynamic light scattering (DLS), transmission electron microscopy (TEM), grazing incidence X-ray diffractometry (GI-XRD) and atomic force microscopy (AFM). TEM and DLS data confirm the formation of crystalline ZnO nanoparticles tethered on top of the virus template. GI-XRD investigations exhibit an orientated nature of the deposited ZnO film along the c-axis. FET devices fabricated using the zinc oxide mineralized virus template material demonstrates an operational transistor performance which was achieved without any high-temperature post-processing steps. Moreover, a further improvement in FET performance was observed by adjusting an optimal layer thickness of the deposited ZnO on top of the TMV. Such a bio-inorganic nanocomposite semiconductor material accessible using a mild and straightforward microwave processing technique could open up new future avenues within the field of bio-electronics.
Keywords: field-effect transistor; microwave synthesis; molecular precursor; thin film transistor; tobacco mosaic virus; zinc oxide